2018
DOI: 10.1111/bjh.15608
|View full text |Cite
|
Sign up to set email alerts
|

Venous thromboembolism and women's health

Abstract: Pregnancy increases the risk of VTE by 4-to 5-fold, spanning all three trimesters and peaking during the postpartum period. VTE complicates 1-2 per 1000 pregnancies (Heit, 2005) and remains the leading direct cause of maternal death at 1Á13 per 100 000 pregnancies [95% confidence interval (CI) 0Á74-1Á65], accounting for 12Á9% of maternal deaths in the UK between (Knight et al, 2017. Risk factors and prevention of pregnancy-associated VTE have been previously reviewed in detail by Guimicheva et al (2015), and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 108 publications
0
23
0
Order By: Relevance
“…The authors report more bleeding in women compared to men, reflective of a higher mg/kg dose of rivaroxaban in women (0·25 mg/kg) relative to men (0·21 mg/kg), P < 0·05, with the dose correlating with rivaroxaban concentrations: median rivaroxaban trough concentration was 12 ng/ml vs. 18 ng/ml in men and women, respectively. The bleeding observed in women was also driven by abnormal uterine bleeding (AUB), which appears to be more common, or more commonly reported, with DOACs compared to traditional anticoagulants (Speed et al , ).…”
Section: What Evidence Has Been Reported From the Real‐world?mentioning
confidence: 99%
See 1 more Smart Citation
“…The authors report more bleeding in women compared to men, reflective of a higher mg/kg dose of rivaroxaban in women (0·25 mg/kg) relative to men (0·21 mg/kg), P < 0·05, with the dose correlating with rivaroxaban concentrations: median rivaroxaban trough concentration was 12 ng/ml vs. 18 ng/ml in men and women, respectively. The bleeding observed in women was also driven by abnormal uterine bleeding (AUB), which appears to be more common, or more commonly reported, with DOACs compared to traditional anticoagulants (Speed et al , ).…”
Section: What Evidence Has Been Reported From the Real‐world?mentioning
confidence: 99%
“…The authors report more bleeding in women compared to men, reflective of a higher mg/kg dose of rivaroxaban in women (0Á25 mg/kg) relative to men (0Á21 mg/kg), P < 0Á05, with the dose correlating with rivaroxaban concentrations: median rivaroxaban trough concentration was 12 ng/ml vs. 18 ng/ml in men and women, respectively. The bleeding observed in women was also driven by abnormal uterine bleeding (AUB), which appears to be more common, or more commonly reported, with DOACs compared to traditional anticoagulants (Speed et al, 2018). Testa et al (2018) have reported analysis from the START laboratory registry, where 565 consecutive anticoagulation-na€ ıve patients with AF had trough DOAC concentrations measured to evaluate the relationship between concentration and thromboembolic events.…”
Section: What Can Be Learnt From the Clinical Trials Regarding Doac Cmentioning
confidence: 99%
“…Among these, Factor V Leiden (FVL, R506Q variant) causes resistance of FV to protein C inhibition; the G20210A variant of prothrombin enhances the synthesis and the activity of Factor II (FII), and the C677T variant of methylene-tetrahydrofolate reductase (MTHFR) impairs the activity of the enzyme, causing an increase in serum homocysteine. In addition to these well-known prothrombotic gene variants, other variants that are thought to play a role in some forms of venous thrombosis include FV H1299R (FVR2), MTHFR A1298C, factor XIII (FXIII) V34L, human platelet antigen (HPA)-1 L33P, beta-fibrinogen -455G>A and plasminogen activator inhibitor (PAI)-1 4G/5G variants [5,10].…”
Section: Introductionmentioning
confidence: 99%
“…[5] In the UK, VTE is the leading direct cause of maternal death (12.9% of patients between 2013 and 2015) and the fifth most common cause of death overall in pregnancy. [6] Approximately 80% of venous thrombotic events are deep-vein thrombosis (DVT) and 20% pulmonary embolism. [7] The risk of VTE increases from the time of conception, with the highest risk at the time of delivery and immediately thereafter, especially in the first 3 -6 postpartum weeks, with approximately half of VTE events occurring during that period.…”
Section: How Many Patients Develop Vte In Pregnancy?mentioning
confidence: 99%